Penerapan Pijat Endorphin Terhadap Tingkat Nyeri Pada Ibu Post Partum Dengan Riwayat Persalinan Tindakan Sectio Caesarea di Ruang Cempaka RSUD dr Soehadi Prijonegoro Sragen - Danis Putri Lestari; Anjar Nurrohmah; Neny Utami (PPNI UNIMMAN, 2024)
Sectio caesarea is an artificial birth that is carried out by making an incision in the abdominal wall and uterine wall. After a caesarean section operation, the mother will feel pain and have an impact that will limit the mother's mobility. One way of non-pharmacological management to reduce post-cesarean section pain is by doing endorphin massage. To determine the results of the implementation of endorphin massage on the level of pain in post partum mothers with a history of caesarean section delivery in the Cempaka ward of RSUD dr. Soehadi Prijonegoro Sragen. This research is a descriptive study in the form of a case study which was carried out on 2 respondents who were mothers post caesarean section by doing endorphin massage for 3 consecutive days with a frequency of 1x a day for 20 minutes. The assessment of the pain scale for the two mothers post sectio caesarea on the first day was on a moderate pain scale and on the third day after implementing endorphin massage, the respondents' pain scale decreased to a mild pain scale. There was a decrease in pain levels before and after endorphin massage was given to mothers post caesarean section in the Cempaka RSUD dr Soehadi Prijonegoro Sragen.